Debt, economic growth and threshold effects: Evidence from developing countries - Ibañez Martín, María María (2024)
Purpose: Most empirical papers on threshold effects between debt and growth focus on developed countries or a mix of developing and developed economies, often using public debt. Evidence for developing economies is inconclusive, as is the analysis of other threshold effects such as those probably caused by the level of relative development or the repayment capacity. The objective of this study was to examine threshold effects for developing economies, including external and total debt, and identify them in the debt-growth relation considering three determinants: debt itself, initial real GDP per capita, and debt to exports ratio. Methods: We used a panel threshold regression model (PTRM) and a dynamic panel threshold model (DPTM) for a sample of 47 developing countries from 1970 to 2019. Findings: We found (a) no evidence of threshold effects applying total debt as a threshold variable; (b) one critical value for external debt of 42.32% (using PTRM) and 67.11% (using DPTM), above which this factor is detrimental to growth; (c) two turning points for initial GDP as a threshold variable, where total and external debt positively affects growth at a very low initial GDP, it becomes non-significant between critical values, and it negatively influences growth above the second threshold; (d) one critical value for external debt to exports using PTRM and DPTM, below which external debt positively affects growth and negatively above it. Conclusions: The outcome suggests that only poorer economies can leverage credits. The level of the threshold for the debt to exports ratio is higher than that found in previous literature, implying that the external restriction could be less relevant in recent periods. However, the threshold for the external debt-to-GDP ratio is lower compared to previous evidence.